Clinical study of 19 patients with SCN8A‐related epilepsy: Two modes of onset regarding EEG and seizures. (26th April 2019) - Denis, Julien; Villeneuve, Nathalie; Cacciagli, Pierre; Mignon‐Ravix, Cecile; Lacoste, Caroline; Lefranc, Jeremie; Napuri, Sylvia; Damaj, Lena; Villega, Frederic; Pedespan, Jean‐Michel; Moutton, Sebastien; Mignot, Cyril; et al.
Summary: Objective: To describe the mode of onset of SCN8A ‐related severe epilepsy in order to facilitate early recognition, and eventually early treatment with sodium channel blockers. Methods: We reviewed the phenotype of patients carrying a mutation in the SCN8A gene, among a multicentric cohort of 638 patients prospectively followed by several pediatric neurologists. We focused on the way clinicians made the diagnosis of epileptic encephalopathy, the very first symptoms, electroencephalography (EEG) findings, and seizure types. We made genotypic/phenotypic correlation based on epilepsy‐associated missense variant localization over the protein. Results: We found 19 patients carrying a de novo mutation of SCN8A, representing 3% of our cohort, with 9 mutations being novel. Age at onset of epilepsy was 1 day to 16 months. We found two modes of onset: 12 patients had slowly emerging onset with rare and/or subtle seizures and normal interictal EEG (group 1). The first event was either acute generalized tonic–clonic seizure (GTCS; Group 1a, n = 6) or episodes of myoclonic jerks that were often mistaken for sleep‐related movements or other movement disorders (Group 1b, n = 6). Seven patients had a sudden onset of frequent tonic seizures or epileptic spasms with abnormal interictal EEG leading to rapid diagnosis of epileptic encephalopathy. Sodium channel blockers were effective or nonaggravating in most cases. Significance: SCN8A is the third most prevalent early onset epileptic encephalopathy gene and is associated with two modes of onset of epilepsy.